2014
DOI: 10.1007/s10897-014-9688-5
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes About Internet Support Groups Among Adolescents and Young Adults with Neurofibromatosis Type 1 and their Parents

Abstract: Youth with neurofibromatosis type 1 (NF1) have multiple, complex symptoms associated with physical, social-emotional, and cognitive difficulties. In addition, caring for a child with NF1 can be extremely challenging for parents. Since research with other chronic illness populations suggests that social support, including internet support groups (ISGs), can be beneficial, this survey study aimed to determine the attitudes and preferences of adolescents and young adults with NF1 and parents of a child with NF1 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
(34 reference statements)
0
11
0
2
Order By: Relevance
“…The PI occasionally responded to participants' posts to try to keep the thread active, and answered questions posed to the health professional within 48 h. More complex medical questions were referred to the nurse-practitioner for responses. Topics were based on the survey results described previously (Martin et al 2014; see Table 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PI occasionally responded to participants' posts to try to keep the thread active, and answered questions posed to the health professional within 48 h. More complex medical questions were referred to the nurse-practitioner for responses. Topics were based on the survey results described previously (Martin et al 2014; see Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…Other positive outcomes include satisfaction with participation, improved parent-child relationships, and hopefulness (Baum 2004). While we are unaware of any studies of ISGs conducted with parents of children with NF1, a recent survey by our group indicated that considerable percentages of these parents were likely or very likely to use an ISG to find out about research studies (87 %), talk to other parents of children with NF1 (67 %), and get answers to questions about NF1 (50 %; Martin et al 2014). Parents further indicated interest in a discussion forum to post messages for a health professional (67 %) and other parents of children with NF1 (67 %).…”
Section: Positive Impact Of Social Support Among Parents Of Children mentioning
confidence: 98%
“…Com relação a NF1 em crianças e adolescentes também é alarmante o prejuízo no desenvolvimento psicológico, cognitivo e de aprendizado desses indivíduos, que neste momento de suas vidas encontram-se em idade escolar e em uma fase de construção de relações sociais, de desenvolvimento de sua inteligência, discernimentos, elaboração de pensamentos, raciocínio, resolução de problemas entre outras funções neuropsíquicas. Além de todo o prejuízo no ensino, crescimento e aperfeiçoamento intelectual, os portadores de NF1 apresentam maiores chances de desenvolver depressão e isolamento social, pelo preconceito sofrido devido à doença 16 . Estima-se que, dentre os pacientes com NF1, até 30% apresentam quadro compatível com transtorno de déficit de atenção e hiperatividade (TDAH) 4 , e até 60 % das pessoas com NF1, mostram problemas de aprendizagem quando comparadas com as pessoas em geral e irmãos não afetados 17 .…”
Section: Fisiopatologiaunclassified
“…Estima-se que, dentre os pacientes com NF1, até 30% apresentam quadro compatível com transtorno de déficit de atenção e hiperatividade (TDAH) 4 , e até 60 % das pessoas com NF1, mostram problemas de aprendizagem quando comparadas com as pessoas em geral e irmãos não afetados 17 . Além disso, existem estudos que demonstram que os próprios pais e cuidadores possuem um risco maior de desenvolver problemas psiquiátricos, como ansiedade, depressão, principalmente quando não conseguem lidar com esta situação e/ou auxiliar seus filhos a conviverem bem com a doença, provocando uma diminuição do papel social, aumento do estresse dos pais e até mesmo refletindo em uma piora do quadro psicológico e comprometimento neurológico dos seus filhos com NF1 16 .…”
Section: Fisiopatologiaunclassified
“…However, these have largely included parents of children not adolescents (Martin et al, 2017), and those with disabilities, not somatic diseases. In particular, research has shown that social-emotional needs of youth with NF1 and their families can be addressed through internet-delivered interventions (Martin et al, 2014). Although it is crucial to provide parents with a support system and resources to help them in caring for their sick child, there is a dearth of peer support interventions for parents of adolescents with a CC (Shilling et al, 2013) or programs that involve them as 'transition experts' (Kingsnorth et al, 2011).…”
Section: Introductionmentioning
confidence: 99%